Soulshaping a journey of self-creation - Brown, Jeff 1962- (North Atlantic Books, 2009)
"The story of a brilliant young trial lawyer who struggled to find his true path, this engaging, inspirational memoir takes readers through profoundly human terrain--unresolved emotional issues, economic obstacles, confusion, self-doubt, and what the author calls "the school of heart knocks"--on a soul-searching journey toward heart-consciousness and spiritual authenticity" --Provided by publisher.